2007
DOI: 10.1016/j.otohns.2007.05.010
|View full text |Cite
|
Sign up to set email alerts
|

The Rising Incidence of Methicillin‐Resistant Staphylococcus Aureus in Pediatric Neck Abscesses

Abstract: The incidence of MRSA in pediatric neck abscesses is increasing dramatically. MRSA and MSSA usually infect younger patients in the lateral locations. Clinical courses were similar in all groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 16 publications
3
46
0
Order By: Relevance
“…Both of our patients who had mediastinitis and septicaemia had MRSA, and 2 patients with stridor had MRSA. In a retrospective review of paediatric neck abscesses, Thomason et al [21] found 3 cases of mediastinitis associated with MRSA deep neck space infections. Wright et al [22] reported that 75% (6/8) of children with positive MRSA cultures from retropharyngeal abscesses developed mediastinitis.…”
Section: Discussionmentioning
confidence: 99%
“…Both of our patients who had mediastinitis and septicaemia had MRSA, and 2 patients with stridor had MRSA. In a retrospective review of paediatric neck abscesses, Thomason et al [21] found 3 cases of mediastinitis associated with MRSA deep neck space infections. Wright et al [22] reported that 75% (6/8) of children with positive MRSA cultures from retropharyngeal abscesses developed mediastinitis.…”
Section: Discussionmentioning
confidence: 99%
“…[1617] The retropharyngeal abscesses can extend down into the mediastinum and may be associated with jugular vein thrombosis, similar to the classic Lemierre’s syndrome. An increasing number of patients with periorbital and orbital infections as well as other infections related to eye structures caused by CA-MRSA are being encountered in children and adults.…”
Section: Introductionmentioning
confidence: 99%
“…Out of 12 patients with complications 8 patients had MRSA infection .Both of our patients who had mediastnitis had MRSA and 4 patients out of 5 patients with upper airway obstruction had MRSA, one patient with sepsis had MRSA. Patient with IJV thrombosis had MRSA .In a retrospective review of pediatric neck abscesses, Thomason et al [8] found 3 cases of mediastinitis associated with MRSA deep neck space infections. Shah et al [25] reported that out of 4 paediatric patients with deep neck space infection with mediatinitis two had MRSA isolated .Wright et al [32] reported that 75% (6/8) of children with positive MRSA cultures from retropharyngeal abscesses developed mediastinitis.…”
Section: Complicationsmentioning
confidence: 99%
“…Rare cases due to Enterobacter, Enterococcus, Proteus, Propionobacter, Pseudomonas and Candida have also been reported [6]. The increasing isolation of community-acquired Methicillin-Resistant Staphyloccoal Aureus (MRSA) in paediatrics head and neck abscesses has been a major focus of the current literature [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation